(untitled) (Research, Society and Development, 2021)
Gingival hyperplasia is associated with several factors, such as chronic inflammation due to the large accumulation of biofilm and medications including anticonvulsants. The aim of this study is to report a clinical case of a 4-year-old spastic quadriplegic cerebral palsy patient with gingival hyperplasia in the palatal region of the upper teeth induced by the use of high doses of anticonvulsant medications. The patient attended the Dental Assistance Center for People with Disabilities, with fibrotic gingival hyperplasia in the upper posterior region, covering the dental crowns on the palatal and occlusal surfaces. Oral hygiene instructions were previously carried out using chlorhexidine gluconate solution (0.12%) on the teeth with the aid of a cotton swab, twice a day for seven days, to reduce bacterial plaque levels and control periodontal inflammation. Gingivectomy was performed using a gallium aluminum arsenide diode laser (GaAlAs; 808±10 nm, 2.5 W output power, continuous mode). Following the surgical procedures, photobiomodulation therapy was performed with a low-level aluminum gallium indium phosphide diode laser (InGaAlP; 660±10 nm, 100 mW, 3 J) at three points (anterior, middle and posterior region of surgical wound). The patient returned at 7 and 30 days after surgery presenting accelerated wound healing. It was concluded that the high-level diode laser associated with photobiomodulation therapy were effective for performing a conservative and safe procedure in a patient with severe neurological disorder.